Endorsement and Condonation of Sexism in Intimate Relationships: The Role of Humour in Comedy Television Shows - Wandinger,Elisa (2020)
The objective of this study was to investigate potential differences in gender and place of origin on intimate partner violence (IPV) attitudes, self-silencing beliefs, and sexist and feminist measures in a sample of young adults between 18 and 30 years. Furthermore, it examined whether exposure to videos containing either sexist or feminist humour impacted participants’ level of IPV attitudes, self-silencing beliefs, sexist and feminist attitudes as compared to neutral humour. In an online, quasi-experimental design 80 participants were randomly assigned to three conditions (viewed sexist, feminist, or neutral humour) and subsequently presented with questionnaires related to self-silencing beliefs, intimate partner violence attitudes, modern sexism, commitment to social change, and self-identification as a feminist. Mean comparison tests showed no statistically significant difference between Scandinavian and non-Scandinavian subjects. Gender differences have been found, with women being more likely to identify as feminists (U = 439, p = .002) and being more committed to social change, t (78) = -2.206, p = .030. No significant effect of the priming manipulation on either IPV attitudes or self-silencing beliefs was detected using ANOVA and Kruskal Wallis tests. Female subjects scored higher on identification with and commitment to feminist causes than males. Moreover, identification with a feminist label was associated with an increased commitment to feminist action. Short exposure to different types of humour did not have any immediate impact on any outcome measures. The relationship between sexist and IPV attitudes and IPV behaviours is complex and needs to be further investigated.
Keywords: Intimate partner violence attitudes; self-silencing; sexist attitudes; feminist attitudes; sexist humour; feminist humour